Local Wisdom and Javanese Politeness in Service Encounters around Central Java Universities - Purnomo, Budi (Media Publikasi Cendekia Indonesia, 2025)
This study explores how Javanese politeness values, or unggah-ungguh, shape communication between waiters and guests in student cafés around leading universities in Semarang, Salatiga, and Surakarta, Central Java. Despite the increasing recognition of intercultural communication in hospitality studies, little attention has been paid to the role of local politeness systems in shaping service interactions. The study aimed to identify how Javanese politeness values are expressed and negotiated in daily hospitality encounters and how these practices influence customer satisfaction. Participants consisted of twenty-four café waiters and six managers, recruited through purposive sampling based on their fluency in Javanese and direct involvement in customer service. Data were collected through participatory observations, semi-structured interviews, and informal group discussions, and analyzed using a thematic qualitative approach. The analysis focused on six key values of Javanese etiquette: sumanak (friendliness), sabar lan sareh (patience and calmness), tepa slira (empathy), andhap asor (humility), empan papan (situational appropriateness), and nuju prana (pleasing others). The findings reveal that consistent application of these values fosters harmonious interaction, strengthens relational bonds, and creates a culturally distinctive atmosphere in the cafés. The study concludes that Javanese politeness functions as a communicative strategy that integrates professionalism with local wisdom, offering insights for culturally grounded hospitality training and intercultural communication research.